2005
DOI: 10.1159/000085340
|View full text |Cite
|
Sign up to set email alerts
|

Baseball Injuries

Abstract: Objective: To identify the frequency of injury in youth baseball, risk factors for these injuries, and possible prevention measures to reduce the frequency or severity of these injuries. Data Sources: Information was collected from all known epidemiologic and intervention studies published in the peer-reviewed medical and scientific literature as it applies to youth baseball injuries. Main Results: The frequency and severity of youth baseball injuries have remained relatively consistent over time. Risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…8 We also found that pitchers were the most common position with shoulder injuries that required surgery, possibly because of the repetitive motions. We found that softball pitchers were injured only half as often as baseball pitchers.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…8 We also found that pitchers were the most common position with shoulder injuries that required surgery, possibly because of the repetitive motions. We found that softball pitchers were injured only half as often as baseball pitchers.…”
Section: Discussionmentioning
confidence: 63%
“…4 This study found that a higher proportion of baseball shoulder injuries lasted 7 to 21 days (42%) compared with a previous study that found that 27% of shoulder injuries resulted in Ͼ5 days' time loss. 8 Although this may suggest that baseball shoulder injuries are increasing in severity over time, additional research is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations